Hereditary and familial cancer. Issue 4 (April 2021) - McCartan, Damian P.; Chatterjee, Sumohan
Abstract: Advances in both access to and the technology underpinning next-generation sequencing have provided a formidable basis for the evaluation of individuals and families recognized as having a potential hereditary cancer. This article focuses on the most clinically relevant hereditary cancer predisposition syndromes such as hereditary breast and ovarian cancer syndromes and hereditary colorectal cancer. It also reviews current best practice in both surveillance for affected individuals as well as an providing an overview of the available risk-reduction strategies for affected individuals.